Additional effects of herbal medicine combined with bisphosphonates for primary osteoporosis: a systematic review and meta-analysis - Yoo, Young-Seo; Kim, Min-Gyeong; Park, Hee-Joo; Chae, Min-Young; Choi, Yu-Jin; Oh, Chae-Kun; Son, Chang-Gue; Lee, Eun-Jung (Frontiers in Pharmacology, 2024)
Background: Osteoporosis (OP) is a significant medical issue associated with population aging. Recent research on herbal medicines (HMs) for OP has been increasing, with these therapies sometimes used in conjunction with bisphosphonates (BPs), the standard treatment for OP. We conducted a systematic review and meta-analysis to evaluate the effects of combining HMs with BPs on improving bone mineral density (BMD) in patients with primary OP. Methods: We searched nine databases—PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang, KISS, Kmbase, Science On, and Oasis—up to August 31, 2023. We selected randomized controlled trials (RCTs) comparing BMD between HMs plus BPs and BPs alone in primary OP. A meta-analysis with BMD as the primary outcome was performed using RevMan version 5.4. Study quality and evidence certainty were assessed through Cochrane's risk of bias2 and GRADE. Results: Out of 43 RCTs involving 4,470 participants (mean age 65.8 ± 6.6 years), 35 RCTs with 3,693 participants were included in the meta-analysis. The combination of HMs and BPs was found to be more effective in improving BMD compared to BPs alone, with improvements of 0.10 g/cm² at the lumbar spine (33 RCTs, 95% CI: 0.07–0.12, p < 0.001, I2 = 93%) and 0.08 g/cm² at the femoral neck (20 RCTs, 95% CI: 0.05–0.12, p < 0.001, I2 = 94%), though this result was associated with high heterogeneity, high risk of bias, and very low certainty of evidence. Conclusion: Our data suggest the possibility that combining HMs with BPs may improve BMD in primary OP more effectively than using BPs alone. However, the results should be interpreted with caution due to the high heterogeneity and low quality of the studies included in the review. Therefore, further well-designed RCTs are needed to confirm these findings.